Visualization of He II boiling process under the microgravity condition for 4.7 s by using a drop tower experiment. (January 2018) - Takada, Suguru; Kimura, Nobuhiro; Pietrowicz, Sławomir; Grunt, Krzysztof; Murakami, Masahide; Okamura, Takahiro
Abstract: Superfluid helium (He II) has been utilized in space projects such as in the X-ray telescope, where it served as the heat sink of adiabatic demagnetization refrigerators. The study of He II boiling under microgravity might contribute to the construction of an important database facilitating the design of future space missions. Therefore, in this study, a visualization experiment of He II boiling was conducted under microgravity conditions by using the drop tower located at ZARM (Center of Applied Space Technology and Microgravity) in Bremen. The ZARM drop tower can provide up to 4.7 s of microgravity conditions in the utilized operation mode. The behavior of thermally induced bubbles during their growth and shrinkage was visualized using two high-speed cameras. A thin manganin wire was utilized as the heater. During the free fall period, the visualized bubble closely approached a steady state. The behavior can be roughly calculated using a simple equation based on kinetic theory.